NTF3 Correlates With Prognosis and Immune Infiltration in Hepatocellular Carcinoma - Liu, Rongqiang; Li, Rongqi; Yu, Haoyuan; Liu, Jianrong; Zheng, Shiyang; Li, Yang; Ye, Linsen (Frontiers in Medicine, 2021)
Background: The potential role of Neurotrophic factor-3(NTF3) in liver cancer is unknown. Therefore, we aimed to explore the clinical value of NTF3 in hepatocellular carcinoma (HCC). Methods: We used a variety of databases to analyze the expression, relationship with prognosis and immune significance of NTF3 in liver cancer through bioinformatics. Results: NTF3 was low expressed in HCC and was an independent prognostic factor in patients with HCC. CIBERSORT analysis indicated that NTF3 expression was positively correlated with CD4+ cells, mast cells, NK cells, macrophages and B cells in the tumor microenvironment. Furthermore, we found that NTF3 expression was negatively correlated with the immune checkpoints PD-L1, TIGIT and TIM-3. Functional network analysis revealed that NTF3 regulates HCC progression through a variety of cancer-related kinases, transcription factors and signaling pathways. Conclusions: We demonstrate that NTF3 correlates with prognosis and immune infiltration in HCC.